Young «parking signallers» (arrumadores): survival in the clutches of drug addiction - Machado Pais, José (2001)
Often looked at sideways by those who cross their path, young car «parking signallers» are the object of research which deserves to be looked at head on by sociology, despite their apparent social irrelevance. How is a «parking signaller» born? Why does he choose such a way of life? What are the tricks of the trade of car parking and so making money? How does the «stigma» associated with young «parking signallers» come about? How does the identity of young people surviving in the clutches of drug addiction evolve (and degenerate)?